Synthesis, Characterization and Antimicrobial Studies of Some Azo-Compounds - Yadav, Pramod Kumar (Academic Voices: A Multidisciplinary Journal, 2018)
Two azo-compounds, azobenzene-4, 4′-dicarboxylic acid 1 and 4-(2-hydroxy-naphthalen-1-ylazo)-benzoic acid 2 were synthesized for study of their antibacterial activity. Structures of the two compounds were confirmed by NMR, IR and elemental analysis. Antibacterial activity of the compounds was tested by disk diffusion method against the bacteria strains Staphylococcus aureus and Escherichia coli. The compound 1 was moderately active while 2 was highly active against all the bacteria species tested. Academic Voices Vol.6 2016: 24-27